2021
DOI: 10.3390/app11136189
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Analysis of the Effects of the Structure Shape and Orientation of Kelvin Cell Porous Structures during Air Forced Convection

Abstract: In recent years, in order to counteract the growth of environmental pollution and the contemporary scarcity of various energy sources, researchers have proposed innovative and efficient solutions for heat transfer applications. Extended surfaces, which can involve the use of fins, open cell metal foams, etc., have been demonstrated to be promising solutions. Open cell metal foams consist of structs intersecting at nodes resulting in stochastic oriented cells. Periodic metal foams have also attracted great inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…The PU foam is composed of domains of pure PU and domains of gas, air in the case of open cell foam, and mixture of hydrocarbon or halogenated gases in the other categories of PU foams. The effective behavior of heterogeneous materials depends on their microstructural features, 4 including the properties of the components such as the thermal conductivity 5 and the Young modulus, and their geometry 6 such as the shape, 7,8 the volume fraction of the solid matrix and the gas, the volume fraction of closed and open cells and their distribution 9 and the behavior at the interfaces between the different components. In computational analysis, all these features are modeled with a representative elementary volume (REV) 10 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The PU foam is composed of domains of pure PU and domains of gas, air in the case of open cell foam, and mixture of hydrocarbon or halogenated gases in the other categories of PU foams. The effective behavior of heterogeneous materials depends on their microstructural features, 4 including the properties of the components such as the thermal conductivity 5 and the Young modulus, and their geometry 6 such as the shape, 7,8 the volume fraction of the solid matrix and the gas, the volume fraction of closed and open cells and their distribution 9 and the behavior at the interfaces between the different components. In computational analysis, all these features are modeled with a representative elementary volume (REV) 10 …”
Section: Introductionmentioning
confidence: 99%
“…Several studies use numerical periodic homogenization to compute the effective thermal conductivity either for composite materials 19 or for foams. 20,21 The generation of the REVs is based on a pavement of unit cells: Kelvin cell, 7,22 Gibson and Ashby cell, 10 and the spherical cell. 6,23 Spherical constructions are used to model polymeric foam without considering the struts' shape and dimensions.…”
Section: Introductionmentioning
confidence: 99%
“…The authors found a 44% reduction in the pressure drop and a slight reduction in the heat transfer performances, because of the reduced free stream velocity around the strut. Different geometrical configurations of cylindrical and elliptical struts as well as four struts orientations in Kelvin's foams were studied by Calati et al [15]. The performance evaluation criteria (PEC) [16] of foams with elliptical struts were found to be better than those of circular struts, with a 22% maximum difference between them.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the interconnectedness of the ideal pore structure of typical catalysts should be high. High convection in the tortuous megapores improves mass and heat transport, whereas the degree of interconnectivity corresponds to a decrease in pressure drop. Highly endothermic and exothermic reactions in long, thin reactor tubes, as well as selective partial oxidation with short contact durations, require these advantages .…”
Section: Introductionmentioning
confidence: 99%